Investigation into Carnivorous Feeding Nature of Piranha (Pygocentrus nattereri) under Laboratory Condition in Bangladesh (Progressive Agriculture, 2013)
An experiment was carried out to know the carnivorous feeding nature of piranha (Pygocentrus nattereri) under laboratory condition for a period of 36 days. One-month old nine fish were stocked in nine separate glass aquaria having three feeding treatments each with three replications. Fish were fed with nursery feed (Sabinco feed) in treatment 1 (T1); 50% live + 50% dead small prawns (Macrobrachium rosenbergii) and small fishes (Esomus danricus and Amblypharyngodon mola) in treatment 2 (T2); and 100% live small prawn and fishes in treatment 3 (T3) twice a day at the rate of 10% body weight. The average weight gain was significantly (P